Recalibrating Entrepreneurship Research: Decolonizing and Embracing the Pluralism of Entrepreneurial Activity - Nason, Robert; Muñoz, Pablo; Haugh, Helen; Welter, Friederike; George, Gerard; Prashantham, Shameen (Journal of Management Studies, 2026)
Abstract Entrepreneurship research has long focused on exceptional, high‐growth, venture‐funded firms while overlooking the everyday and modest ventures that make up most entrepreneurial activity. This Special Issue calls for a recalibration of the field by decolonizing its assumptions and embracing its pluralism. We distinguish between conventional entrepreneurship, shaped by ideals of technology‐driven innovation and venture‐capital funded growth, and unconventional entrepreneurship, which reflects diverse and contextually grounded practices. Focusing on everydayness, pluralism, and decolonization, we draw on Santos’ concept of abyssal line to invite a shift from studying outliers to studying the ordinary. Using the metaphor of moving from a microscope to a prism, we call for theories that capture the full spectrum of entrepreneurial life across contexts and cultures. We discuss how papers in this Special Issue exemplify this prism approach and, in doing so, cast new light on how entrepreneurship can be understood, studied, and imagined.